Systemic risk buffer and residential real estate loans: The steering effect of sectoral buffer application - Sebastian Geiger (Deutsche Bundesbank, 2022)
This paper describes the effects of the sectoral application of the systemic risk buffer (SyRB) within the German banking system. The analysis compares a general capital buffer (e.g. CCyB) to the sectoral SyRB (sSyRB) in the context of addressing the risks resulting from residential real estate (RRE) loans. It finds that the sSyRB works in a targeted manner and spares other exposure types (e.g. corporate loans) from disproportionally higher capital charges. By using regression techniques, the paper also quantifies ex ante the expected relative reduction of RRE loans in the banks' portfolios. Specifically, the models find statistically significant evidence that the RRE loan share (relative to corporate loans) could decline by between 1.1 and 4.7 percentage points if the sSyRB is set to 2.00 %.
Keywords: D22; G11; G21; G28; R21; 330; residential real estate; loan portfolio; systemic risk buffer; macroprudential policy; Germany